L’avortement comme trauma : normes et valeurs du récit d’IVG post-légalisation - Charlotte Thevenet (Itinéraires)
While women's experiences of motherhood, violence and sexuality have been of interest to writers and literary researchers alike, the issue of abortion seems to be addressed only in relation to other major concerns, such as trauma. When abortion appears in French-language literature, it is in two forms: either as an autobiographical account, or in an explicitly fictional form. It is the latter that will be examined here, through a comparative study of three contemporary instances of the treatment of abortion in fiction, all three produced after the legalisation of abortion: L'Enfant sacrifié, by Othilie Bailly (1994), Instruments des ténèbres, by Nancy Huston (1996), and Ta grossesse, by Suzanne Duval (2020).This article will question the norms at work in these fictional narratives of abortion. In other words, to what extent do these contemporary works, written by women (some reputed to be feminists, such as Nancy Huston), take up and rework already existing frameworks and commonplaces in order to recount the experience of abortion, in an ongoing negotiation with both conservative and progressive norms shaping representations of abortion? After a foray into autobiographical accounts of abortion, which will allow for a clearer distinction between testimonial and fictional accounts, I will look at the function of abortion in the three novels. Finally, as all three texts belong to different fields of contemporary literature, I will show how they articulate the complex relationship between literary and social values.